(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Knowledge is ever growing. Itgoes unfolding the mysteries of the unknown. As new invention and discoveriesare made, they add to the existing corpus of knowledge. Systematic development ofknowledge is a collective effort. Each individual contributes a small bit ashis share. As one cannot make hiscontribution in any field he wishes to choose any point of time, he has to makesustained effort over a long period. He has to systematicallyproceed from general awareness of all the branches of knowledge to a small areaof research towards the end of his educational process. Many factors areresponsible for men’s educational progress. Today, world is progressing throughvarious trends. In those trends ICT isone; ICT plays a great part in men’s progress. Before moving forward we must have the knowledge of ICT & its impacton our education. ICT is a “diverse set oftechnological tools and resources used to communication and to create,disseminate, store and manage information”. These technologies includecomputers, the internet, broadcasting technologies (radio and television) andtelephony.